Research on the Fusion Positioning Technology of 5G+ Beidou Based on the Federated Kalman Algorithm - Song, Jinliang; Wen, Xin; Liu, Yue; Wang, Dongdong; Guo, Linlang; Liu, Jiaqiang; Sun, Qian; Tong, Haosong; Xiao, Nan; He, Lishuai (Journal of physics. Conference series, 2023)
In the new energy Internet scenario, unmanned patrol navigation of power lines, accurate fault location of power equipment and position monitoring of power towers put forward higher requirements for power location technology. Aiming at the problems of heavy workload, low accuracy and poor real-time performance of the existing power positioning scheme, a fusion positioning technology of 5G+ Beidou based on federated Kalman algorithm is proposed, considering the real-time dynamic differential correction data transmission technology.